1306. Comparison of the Use of Extended and Intermittent Infusion Cefepime and Piperacillin/tazobactam in Non-critically Ill, Obese Patients - Marg, Carolyn (Open Forum Infect Dis, 2020)
BACKGROUND: Obesity rates have dramatically increased over the last several decades, however, there is limited data to guide how antibiotics should be adjusted in obese patients. Physiologic differences including an increased volume of distribution and increased renal clearance may alter their pharmacokinetics and pharmacodynamics and subsequently, their efficacy. For beta-lactams like piperacillin/tazobactam (pip/tazo) and cefepime, extended infusion (EI) maximizes the time above the minimum inhibitory concentration (MIC) for optimal bactericidal activity. This dosing strategy may help decrease variability in achieving the target time above MIC in this patient population and lead to more favorable outcomes. METHODS: This single-center, retrospective, pre-/post- analysis included patients with a body mass index (BMI) > 30 that received EI (infused over 4 hours) or intermittent infusion (II) (infused over 30 minutes) pip/tazo or cefepime between 2/1/2020-4/30/2020 and 2/1/2019-4/30/2019, respectively. The primary outcome was in-hospital, all-cause mortality. Secondary outcomes included clinical success rate and hospital length of stay (LOS). RESULTS: During the evaluation periods, 98 patients met inclusion criteria (EI, N=53; II, N=45). Mean BMI was not statistically different between groups (EI, 36.0 kg/m2 [30.1-46.3]; II, 36.5 kg/m2 [30-48]). There were no cases of mortality in either group. The mean LOS in the II group was 13 days compared to 11.5 days in the EI group [95% CI -4.14-7.04; p=0.606]. After excluding one outlier of 104 days in the EI group, the average LOS was 9.5 days [95% CI: -0.87-7.33; p=0.121]. Markers of clinical success including time to resolution of fever (II: 47 hours; EI: 34 hours; p=0.216) and time to resolution of leukocytosis (II: 2 days; EI: 3.8 days; p=0.089) were not significantly different between groups. CONCLUSION: The use of EI pip/tazo and cefepime was not associated with any differences in in-hospital, all-cause mortality, hospital LOS, or clinical success when compared to the use of II pip/tazo and cefepime. The lack of significant differences between groups may be attributable to the small sample size limiting the ability to detect a difference, especially regarding hospital LOS. DISCLOSURES: All Authors: No reported disclosures